2015
DOI: 10.1586/17434440.2015.1015988
|View full text |Cite
|
Sign up to set email alerts
|

Economic and clinical benefits of radiofrequency ablation versus hysterectomy in patients suffering from menorrhagia: a retrospective analysis with German health claims data

Abstract: RFA should more often be considered a relevant treatment option both from an economic and a medical point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Figure 2 shows that 21 studies (60.0%) evaluated health care programs such as disease management programs which were assessed in 8 studies (22.9%) alone [ 21 , 25 27 , 37 , 39 , 43 , 49 ]. Evaluations were also performed on pharmaceuticals in 8 studies (22.8%) [ 30 , 35 , 41 , 44 48 ] and medical products or procedures in 6 studies (17.1%) [ 2 , 3 , 23 , 24 , 36 , 50 ]. Funding can mainly be ascribed to industry ( n = 15, 42.9%) – generally the involved health insurance fund or product manufacturer – or public sources ( n = 8, 22.9%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows that 21 studies (60.0%) evaluated health care programs such as disease management programs which were assessed in 8 studies (22.9%) alone [ 21 , 25 27 , 37 , 39 , 43 , 49 ]. Evaluations were also performed on pharmaceuticals in 8 studies (22.8%) [ 30 , 35 , 41 , 44 48 ] and medical products or procedures in 6 studies (17.1%) [ 2 , 3 , 23 , 24 , 36 , 50 ]. Funding can mainly be ascribed to industry ( n = 15, 42.9%) – generally the involved health insurance fund or product manufacturer – or public sources ( n = 8, 22.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining studies, 4 (11.4%) used claims data from several different health insurance funds – 2 of which (5.7%) specified which funds were involved [ 45 , 46 ]. The other two studies (5.7%) referred to a SHI database [ 24 , 36 ]. Finally, two studies (5.7%) did not specify which individual fund supplied the data [ 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed following an analysis that reported the clinical and economic benefits of RFA compared with hysterectomy in women with menorrhagia; Kessel et al reported a total savings of €1,771 within 2 years after the first treatment when treating menorrhagia with RFA instead of hysterectomy. 21 …”
Section: Discussionmentioning
confidence: 99%